Implementation of Yoga Gymes to Improve Students Concentration in Kindergaten of Muslimat Nahdlatul Ulama 32 Nurul Hikmah Jatimulyo Village Kebumen - Nadzifatus Sangadah; K Kusumastuti (Prosiding University Research Colloquium, 2019)
Background: Children who have difficulty and disruption in concentrating while studying in the classroom will find it difficult to do the assignments given by the teacher. To overcome this can be done with yoga exercises. According to Wirmayani and Supriyadi (2017) students who do yoga will be more successful in school, both physically and cognitively. According to Nisa (2016) the concentration of learning can significantly improve learning achievement.Purpose: Applying yoga exercises to improve concentration in toddlers.Method: The researcher used a descriptive qualitative method using a case study approach. Participants consisted of 5 students from TK MNU 32 Nurul Hikmah Jatimulyo Village, Alian, Kebumen. Data obtained from written tests. The instrument used by the author in applying the observation sheet regarding the concentration of children.Results: Before the implementation of yoga exercises all participants 5 (100%) had poor concentration categories. Each participant is given care by applying yoga gymnastics 6 times in a span of 3 weeks with 2 training sessions per week, each training session lasts 20-30 minutes. After the application of yoga exercises, 3 participants with a level of concentration in the category were quite good (60%), and 2 participants with a level of concentration in the good category (40%).Conclusion: The application of yoga exercises is effective in increasing concentration in toddlers.